(untitled) (Asian Business Research, 2022)
The quality of accounting information of listed companies is an important factor affecting corporate performance. This paper selects 3460 listed companies in China from 2005 to 2019 as the research object, and studies the relationship between accounting information quality and corporate performance of listed companies. Through empirical analysis, it is found that improving accounting information quality of listed companies can effectively improve corporate performance. And the improvement of accounting information quality of non-state-owned listed companies is more significant than that of state-owned listed companies. This study provides a new perspective for Chinese listed companies to carry out accounting information quality management, and may also contribute to the healthy development of listed companies in other countries and regions.